Strategic Alliance Design Formulation of 'Aisyiyah Kudus Hospital with Muhammadiyah’s Clinics in Kudus District Indonesia - Fitri Kinanti; Merita Arini (Universitas Aisyah Pringsewu, 2023)
A strategic alliance is a form of long-term cooperation, between two or more organizations that aims to improve services and profits by utilizing shared resources where the more cooperation or alliances that are built, the more partnership and communication actions will be in accordance with the benefits and goals you want to be achieved. This research aims to design a strategic alliance for AUMAKES in Kudus Regency. This type of research is a qualitative approach with data collection methods using observation techniques and in-depth interviews (IDIs). The informants were 1 hospital leader, four clinics leaders, and 1 Majlis of Public Health or Majelis Pembina Kesehatan Umum (MPKU) of Muhammadiyah Regional Council or Pimpinan Daerah Muhammadiyah (PDM) Kudus Regency. The IDIs data were audio recorded, transcribed verbatim, and subjected to content analysis. The study results found that the alliance strategic positioning of AUMAKES Kudus is in the third phase, namely the phase of expanding the relationship and in quadrant I on the Cartesian diagram means proactive or offensive to plan and expand the relationship. Besides that, strategic alliance positioning and several forms of AUMAKES strategic alliances that can be implemented in Kudus Regency include referral systems, human resources, information technology, finance, services, marketing, pharmacy, accreditation and training.With many forms of strategic alliances that can benefit AUMAKES, there needs to be a fast movement and commitment from all parties to realize this strategic alliance immediately.Abstrak: Aliansi strategis suatu bentuk kerjasama jangka panjang, antara dua atau lebih organisasi yang bertujuan untuk meningkatkan layanan dan keuntungan dengan memanfaatkan sumber daya bersama dimana semakin banyak kerjasama atau aliansi yang terbangun, maka akan semakin banyak pula tindakan kemitraan dan komunikasi sesuai dengan manfaat dan tujuan yang ingin dicapai. Banyak cara untuk merumuskan dan merencanakan aliansi strategis ini, salah satunya dengan analisis SWOT terlebih dahulu untuk mengetahui positioning aliansi yang sudah ada sekarang. Selanjutnya, dari hasil analisis tersebut dapat dibuat rancangan aliansi strategis yang disesuaikan dengan outcome yang diinginkan. Tujuan dari penelitian ini adalah untuk membuat rancangan aliansi strategis yang ideal untuk AUMAKES di Kabupaten Kudus. Jenis penelitian ini adalah pendekatan kualitatif dengan metode pengambilan data menggunakan teknik observasi dan wawancara mendalam. Sample merupakan 4 orang pimpinan AUMAKES di Kabupaten Kudus dan 1 orang anggota MPKU PDM Kudus. Data dianalisis dengan teknik analisis konten kualitatif. Pada hasil penelitian didapatkan positioning aliansi strategis dan 10 bentuk aliansi yang dapat diterapkan AUMAKES di Kabupaten Kudus. Dengan banyaknya bentuk aliansi strategis yang bisa menguntungkan AUMAKES, perlu adanya gerakan cepat dan komitmen dari segala pihak untuk segera merealisasikan aliansi stategis ini.